IMPLEMENTATION OF GRANTING HEALTHCARE FACILITIES RIGHTS FOR PREGNANT FEMALE PRISONERS AT CLASS II A SURABAYA WOMEN’S PENITENTIARY - Lestari, Yashinta Dwi; Prasetyo, Dr. Dossy Iskandar (jfpublisher, 2023)
The fulfilment of prisoners’ rights must be granted to every prisoner, including children, men, and women, as stipulated in Law No. 12/1995. Fulfilment of these rights includes the right to receive healthcare and proper food. The treatment between female and male prisoners is quite different, especially for pregnant prisoners. Therefore, this research aims to find out the implementation of granting healthcare facilities to pregnant prisoners in women’s detention centre class IIA Surabaya. This type of research is empirical juridical with a combination of qualitative and quantitative approaches. There are 2 sources of legal material used, such as (1) the primary legal source comes from community legal aid institutions, the right to health pocket book, Law No. 22/2022 on correctional facilities, Law No. 39/1999 on human rights; (2) the secondary legal source comes from the results of filling out questionnaires and interviews. Although the health facilities provided in the detention centre are supportive, some pregnant prisoners stated that the health services provided were inadequate and there was a lack of counselling on pregnancy programmes. Therefore, the detention centre seeks to fulfil the health rights of pregnant prisoners as stated in Law No. 22/2022.